Big Foot and Little Foot - Potter, Ellen, 1963- (Amulet Books, 2018)
"Hugo is a young Sasquatch who longs for adventure. Boone is young boy who longs to see a Sasquatch. When their worlds collide, they become the unlikeliest pair of best friends"--